Case report: Trigeminal neuralgia misdiagnosed as glossopharyngeal neuralgia - Wu, Liangzhe; Xiong, Jinbiao; Huang, Ying; Han, Kunning; Cai, Kunhao; Fu, Xuejun (Frontiers in Neurology, 2023)
Background Trigeminal neuralgia (TN) and glossopharyngeal neuralgia (GPN) are cranial nerve neuralgias with the same clinical manifestations, pathological features, and trigger factors; their affected sites are adjacent. Performing a magnetic resonance imaging (MRI) examination alone can easily lead to a misdiagnosis. Case presentation A 72-year-old man had visited another hospital with severe left-sided tongue pain. On MRI, vascular compression of the glossopharyngeal nerve had been visible, with unclear evidence of trigeminal nerve involvement. He had been diagnosed with left-sided GPN and underwent microvascular decompression (MVD) of the left glossopharyngeal nerve. However, no improvement was observed after surgery. During a second surgery at our hospital, MVD of the trigeminal nerve was performed, and the trigeminal nerve was fully explored and separated. The patient's pain resolved after surgery. Ultimately, the patient was definitively diagnosed with left-sided TN. Discussion and conclusion MVD is currently the most efficacious surgical option for treating cranial nerve neuralgia. To select patients for MVD, having an MRI criteria for identifying true neurovascular compression will be helpful. However, clinicians should focus more on a patient's clinical symptoms and not rely solely on MRI findings. This patient's case can help clinicians distinguish between TN and GPN, improve the understanding of these diseases, avoid misdiagnosis, and reduce the possibility of secondary damage.